Role of Full Correction of Myopia in Regulation of Intra Ocular Pressure in Young Persons - Azfer Ahmed Mirza, Munawar Ahmed, Murtaza Sameen, Mahtab Alam Khanzada Arshad Ali Lodhi (Pakistan Journal of Ophthalmology, 2017)
Purpose: To evaluate effects of full myopic correction on intra ocular pressure (IOP) in young persons. Study Design: Prospective observational clinical study. Place and duration of study: Department of Ophthalmology (LUMHS) from May 2014 to May 2016 Material and methods: By independent simple random sample selection technique in total 65 patients ranging 15- 35 years of either sex having simple spherical myopia -1.0 to -4.0 D, and intraocular pressure 14 to 20 mm Hg, wearing glasses for the first time were enrolled for the study. After verbal / written consent initial refraction was done with auto- refractometer followed by subjective correction. Slit lamp examination of anterior and posterior segment with 90 D A-spheric lens was carried out. Intra-ocular pressure was measured with applanation tonometer. Post corrected visual acuity and back vertex distance was noted. Fully corrected prescription (equally readable in red and green on duochrome test) was given and constant wear was advised. After one week, the refraction was reconfirmed with glasses, and IOP was measured immediately after removing the glasses. Further follow up was done after one month and three months. Each time IOP was measured immediately after removing the glasses. Any complaint was noted and results were compiled. Patients with incomplete follow are not included in data analyses. Results: Out of sixty-five registered patients fifty two completed three months follow up criteria of this study. Among these 52 patients reduction of IOP was observed in 45 (86.54%), and mean reduction of IOP was 2.8790 mm Hg (16.7062%). In remaining 7 (13.46%) patients there was no or little response. Only 10 (19.23%) patients complained of eye strain, which was relieved after few days. After three months follow up data was processed on SPSS version 14.0 and p-value was 0.003 (< 0.05), which is quite significant. Conclusion: Accommodation, which is reduced or totally abolished in myopia, plays important role in regulation of IOP, restoration of accommodation with full myopic correction helps in establishing normal physiology of aqueous humor circulation. Therefore myopia should not be under corrected in young persons, as full correction is more effective in reducing IOP than under correction. Key words: Myopia, refraction, IOP, full correction, Young patients.